2015
DOI: 10.1097/tp.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Hereditary Transthyretin Amyloidosis

Abstract: Long-term survival after Ltx, especially for early-onset TTR Val30Met patients, is excellent. The risk of delaying Ltx by testing alternative treatments, especially in early-onset TTR Val30Met patients, requires consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(129 citation statements)
references
References 28 publications
1
120
1
1
Order By: Relevance
“…Elimination of mutant TTR is the fundamental driver behind liver transplantation for ATTR amyloidosis with polyneuropathy, and the clinical benefits associated with this procedure highlight the potential effect of therapies that can lower hepatic TTR. 20,21 Indeed, the high level of TTR knockdown achieved with revusiran ($90%) is comparable with the reduction in mutant TTR following liver transplantation, with the added advantage of affecting both mutant and WT TTR production. The high potency of revusiran is also particularly promising because a reduction in levels of amyloidogenic protein of only 50% has been associated with clinical benefits in light-chain amyloidosis.…”
Section: Discussionmentioning
confidence: 70%
“…Elimination of mutant TTR is the fundamental driver behind liver transplantation for ATTR amyloidosis with polyneuropathy, and the clinical benefits associated with this procedure highlight the potential effect of therapies that can lower hepatic TTR. 20,21 Indeed, the high level of TTR knockdown achieved with revusiran ($90%) is comparable with the reduction in mutant TTR following liver transplantation, with the added advantage of affecting both mutant and WT TTR production. The high potency of revusiran is also particularly promising because a reduction in levels of amyloidogenic protein of only 50% has been associated with clinical benefits in light-chain amyloidosis.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, the benefits of transplantation may be counterbalanced by the requirement of lifelong immunosuppression, surgical risk in already hemodynamically-compromised patients, and high expense. The literature suggested that liver transplantation in isolation in older adult patients with cardiomyopathy was not effective and combined heart and liver transplantation is usually reserved for younger individuals (41). Additionally, amyloid progression might potentially progress after organ transplant; normal wild-type TTR can build up on previously deposited transthyretin in the heart and nerves, leading to recurrent amyloid cardiomyopathy or progression of polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival after liver transplantation indeed increased to more than 20 years, and the 10-year survival is about 85% [40]. However, this approach is not always successful, because ATTR amyloid sometimes progresses in the heart after liver transplantation.…”
Section: Treatmentmentioning
confidence: 99%
“…It looks as if wild-type ATTR amyloidosis takes over and further progresses in these transplanted patients. Because of this, patients with late disease onset (often males with cardiomyopathy) and patients with non-TTR-Met30 mutations are deemed less eligible for liver transplantation [40,41]. …”
Section: Treatmentmentioning
confidence: 99%